A dohányreklámok szabályozásának változásai a magyar jogban - Pribula, László (Debreceni Jogi Műhely, 2005)
Since the change of the regime the economic role of advertisements has changed significantly. Advertising forms a considerable part of economic activities, the cost of which constitute a growing portion of the expenses of a given enterprise. The mass-appearance of advertisements has altered the relationship between consumers and advertisers, it has restructured consumption habits and the importance of advertising in media.The most significant modification of the Hungarian Advertising Act occurred by (Act I of 2001), which was in large passed with the consent of the advertising profession. The modification introduced the concept of deceptive advertisements, apparent comparative advertisements and special offers. Comparative advertisements were also regulated in a satisfactory way. However, several legal institutions were introduced as well, which should have been included in competition law. In the last two decades actions against unlawful advertisements were largely based on competition law, which restricts advertising activities violating fair competition in general. Advertising Decree and later the Advertising Act regulated the restriction of advertisements of certain goods and services, or defined the restrictions on certain advertising activities. Due to the modification, the role of Competition Act became less significant, since Advertising Act also contains most prohibitions on advertising activities that were defined in the Competition Act. In addition, in the case of violation of regulations on deceptive and comparative advertisements, Advertising Act denoted the Bureau of Competition and the court as chief acting powers, whereas the violation of rules on apparent comparative advertisements falls in the scope of the Consumer Protection Authority.What is more, the (Act I of 2001) “smuggled” the entire prohibition of tobacco advertisements into the Advertising Act, which totally contradicted with the opinion of advertising profession. Thus Hungary, similarly to France, joined the strictest practice in this question. It is also disputable whether such restrictions promote the fight against smoking, and it was certainly disadvantageous that legislation decided in the question without involving the profession, for which there had been no precedents so far.